Karakter Vokasi: Edukasi Tarian Barong Dance Pada Poster Digital Dan Media Promosi Pariwisata Budaya Bali - I Made Darmada; Ngakan Agung Bagus Purwantara; I Nyoman Lodra (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2025)
This research aims to understand the vocational characteristics of the digital poster themed Barong Dance in developing specific skills and expertise. This research is beneficial as a promotional medium to enhance the appeal of Balinese cultural tourism and serves as a reference for other researchers. The digital poster as a promotional tool is designed using graphic design programs such as Canva, CorelDraw, Photoshop, or Illustrator. In Bali, the Barong Dance is an important sacred symbol that portrays the struggle between good and evil, and this dance is not only a part of religious rituals but is also drawn for entertainment in the tourism industry. The focus of this research on the Barong Dance poster is presented in the image of the digital poster as a vocational characteristic. The research method used is qualitative descriptive with data collection through observation, interviews, and documentation.The results of this research are in the form of: digital posters with the theme of barong dance can increase tourist attraction while promoting Balinese culture globally. In addition, it can also contribute to the improvement of Bali's creative economy and sustainable tourism.